Multiomics identifies the endothelial SYNPO2/VNN1 axis as a therapeutic target and validates a microbiota-directed vaccine in atherosclerosis - Lin Chen; Fei Wang; Hui Zhang; Sheng Qin; Kotaro Uchida; Takuya Sugawara; Shintaro Minegishi; Kentaro Arakawa; Ryuta Abe; Ming Sui; Chunjian Li; Kiyoshi Hibi; et al. (Journal of Translational Medicine, 2026)
Abstract Background Gut microbiota (GM) dysbiosis is implicated in atherosclerosis (AS), but its causal mechanisms and actionable therapeutic targets remain elusive. This study aims to identify specific GM-host interactions and translate multiomics findings into clinically relevant therapeutic strategies. Methods We developed an integrative multiomics framework combining bidirectional Mendelian randomization (MR) on large-scale GWAS data, bulk and single-cell transcriptomics, and in vivo validation. MR was used to identify causal microbial taxa. Transcriptomic analyses revealed key endothelial genes. A microbiota-targeted vaccine against Klebsiella aerogenes was developed and tested in ApoE-knockout mice fed a high-fat diet to evaluate its therapeutic efficacy on plaque burden, lipid profiles, and hormonal levels. Results Bidirectional MR identified 38 microbial taxa causally linked to AS (14 risk-enhancing and 24 protective). Integrative transcriptomics pinpointed SYNPO2 (downregulated) and VNN1 (upregulated) as key endothelial genes in AS progression. Single-cell RNA sequencing further defined endothelial cells as central mediators, with SYNPO2 dominating early differentiation and VNN1 driving late-stage inflammation. Drug screening identified estradiol and progesterone as dual-target agents. Notably, K. aerogenes was found to degrade atheroprotective estradiol. Vaccination against K. aerogenes preserved serum estradiol levels, reduced aortic plaque burden by approximately 40%, and improved lipid profiles in mice without disrupting overall gut microbial diversity. Conclusions This study defines a SYNPO2-VNN1 dysregulation axis in endothelial cells as a key driver of AS, exacerbated by GM-mediated estradiol depletion. The K. aerogenes -targeted vaccine represents a novel, precision-based therapeutic approach that preserves vasoprotective estradiol and attenuates atherosclerosis. Our findings establish the GM-immune-endothelial axis as a promising and clinically translatable target for precision cardiology, offering new strategies beyond traditional lipid-centered therapies.